Sanitation-related violence against women in informal settlements in Kenya: a quantitative analysis - Winter, Samantha C.; Johnson, Laura; Dzombo, Millicent N. (Frontiers in Public Health, 2023)
Approximately 3.6 billion people around the world do not have access to safe sanitation options. Those lacking access are not only at risk of diarrheal disease, other tropical diseases, and parasitic infections, they are at greater risk of experiencing violence, particularly women and girls. The burden of lack of access to safe sanitation is disproportionately experienced by women in informal settlements in lower- and middle-income countries, where violence rates tend to be higher and access to sanitation lower. Women lacking access to safe toilets often have to walk long distances to access a facility or open site or use shared toilet facilities, which increase their vulnerability to violence. We explore the prevalence and multilevel factors associated with women’s experiences, observations, and exposure to stories about past-year sanitation-related violence in a probability sample of 500 women in a large informal settlement in Nairobi, Kenya using chi-square tests and multivariate logistic regressions. Findings suggest that social/community engagement and social/cultural beliefs are important considerations for hearing about and observing sanitation-related violence, but less so experiences of sanitation-related violence. Alternatively, individual-level and technological factors may be critical factors in actual experiences of violence. Sanitation-related violence and creating an environment of safety in which women can take care of their sanitation-related needs in ways that also protect them, their families, and their communities is critical for meeting sanitation-related development agendas and goals such as Sustainable Development Goal 6.2 to achieve access to adequate and equitable sanitation and hygiene for all by 2030.